Leadership for dummies - Loeb, Marshall; Kindel, Stephen (Foster City, CA : IDG Books Worldwide, 1999)
This book is not only for would-be chief executive officers or five-star generals, but for anyone with the desire to take the lead.The book shows you how to add leadership skills to your arsenal of personal traits and explains how doing so helps you to achieve more happiness and contentment in all areas of your life.
Includes index.
rpm 13/06/13
Loans
Keywords: Executive ability; Leadership